ASSOCIATION BETWEEN TIME OF INITIATING EMPIRICAL ANTIBIOTIC AND OUTCOMES IN PATIENTS WITH COMMUNITY-ACQUIRED PNEUMONIA - I Gede Ketut Sajinadiyasa; Yogi Haditya; I Ketut Agus Somia (Indonesia Journal of Chest Critical Emergency Medicine, 2026)
ABSTRACT Background: Community-acquired pneumonia (CAP) remains a leading cause of morbidity and mortality worldwide, with a significant burden in Indonesia. Early initiation of empirical antibiotics is considered crucial in improving outcomes, yet evidence has been inconsistent and local data are lacking. Objective of this study is to evaluate the association between the timing of empirical antibiotic initiation and clinical outcomes, specifically mortality and length of hospital stay, among CAP patients at RS Ngoerah, Denpasar. Methods: A prospective observational study was conducted on adult inpatients with CAP between January and June 2024. Patients were stratified into two groups based on antibiotic initiation time: ≤4 hours and >4 hours after admission. Data were analyzed using Chi-square, Logistic regression, and Linier regression to adjust for confounders, including age, sex, comorbidities, and disease severity. Results: A total of 235 patients were enrolled. Early antibiotic initiation (≤4 hours) significantly reduced 30-day mortality compared to delayed administration (>4 hours) (adjusted OR 4,97; 95% CI 1,50–16,47; p<0.05). No statistically significant difference was observed in the length of hospital stay (median 5 vs 5 days; p=0.95). Length of stay was more influenced by comorbidities, and antibiotic used. Conclusion: Empirical antibiotic initiation later than 4 hours is associated with increase mortality in CAP patients, although it does not significantly affect length of hospital stay. These findings highlight the importance of timely antibiotic administration to improve clinical outcomes in CAP. Keywords: community-acquired pneumonia, antibiotics, timing, mortality, hospital stay